Glanzmann’s thrombasthenia: A rare case (Indian Journal of Case Reports, 2019)
Glanzmann’s thrombasthenia is an extremely rare autosomal recessive inherited bleeding disorder characterized by the impaired function of platelets leading to prolonged bleeding time. Patients may present with easy bruising, purpura, epistaxis, menorrhagia and gingival bleeding. Though the disease is rare, the prognosis is usually good with supportive care. Here, we report the case of Glanzmann’s thrombasthenia in a young male who presented with complaints of gum bleeding, epistaxis and a history of easy bruising. The patient improved with symptomatic and supportive care. The patient got discharged and is doing well under regular follow-up.